The Effect of Self-Leadership Strategies on Innovative Work Behaviors among School Teachers (Kesan Strategi Kepemimpinan Kendiri terhadap Tingkah Laku Kerja Inovatif dalam Kalangan Guru Sekolah) (Jurnal Pembangunan Sosial, 2019)
Innovative work behavior has gained considerable attention in the organisational behavior literature. Research on an integrated framework that cover personal predictors of innovative work behavior is still limited specifically among Malaysia government school teachers. This research incorporated the components of an individualâ€™s behavioral (behavior-focused), cognitive (constructive thought pattern and natural reward) and physiological (physical vitality) approach as self-leadership strategies that serve as predictors of innovative work behavior. This research used Revised Self-Leadership Questionnaires (RSLQ) to measure teacherâ€™s self-leadership strategies and Innovative Behavior Scale by Robert and Christopher (2001) was used to measure individualâ€™s innovative behavior. This research utilized quantitative approach where questionnaires were distributed to 250 government school teachers as a sample of the research. Overall, 234 completed questionnaires were usable for data analysis. The data was analyzed by using IBM Statistical Package for Social Science 22 statistical. The findings indicated that behavior focused strategies, constructive thought pattern strategies, natural reward strategies and physiological strategies significantly affected innovative work behavior of government school teachers. The findings of the study may help organizations to increase teachersâ€™ innovative work behavior by improving teachersâ€™ self-leadership strategies at the workplace.AbstrakTingkah laku kerja inovatif telah mendapat perhatian dalam literatur tingkah laku organisasi. Kajian berkaitan modellengkap yang memberikan penekanan kepada elemen tingkah laku kerja inovatif masih terhad khususnya dalam kalangan guru sekolah kerajaan Malaysia. Kajian ini menggabungkan komponen pendekatan tingkah laku (tingkah laku berfokus), kognitif (corakpemikiran konstruktif dan ganjaran semula jadi) dan fisiologikal (kecergasan fizikal) sebagai strategi kepemimpinan diri yang berfungsi sebagai peramal kepada tingkah laku kerja inovatif. Kajian ini juga menggunakanRevision Self-Leadership Questionnaires (RSLQ) untuk mengukur strategi kepemimpinan diri dan Innovative Behavior Scale oleh Robert danChristopher (2001) digunakan untuk mengukur tingkah laku inovatif individu. Kajian ini menggunakan pendekatan kuantitatif di mana borang soal selidik diedarkan kepada 250 guru sekolah kerajaan sebagai sampel kajian. Secara keseluruhan, 234 soal selidik yang lengkap diterima dan digunakan untuk analisis data. Data dianalisis dengan menggunakan IBM Statistical Package for Social Science (SPSS) versi 22. Hasil kajian menunjukkan bahawa strategi tingkah laku berfokus, strategi corak pemikiran konstruktif, strategi ganjaran semula jadi dan strategi fisiologikal mempengaruhi tingkah laku kerja inovatif guru sekolah kerajaan. Penemuan kajian ini dapat membantu organisasi untuk meningkatkan tingkah laku kerja inovatif dalam kalangan guru dengan meningkatkan strategi kepemimpinan diri di tempat kerja.Kata kunci: Kepimpinan diri, tingkah laku kerja inovatif, guru.